Insulating silica gel glass fabric composite material with high tensile strength

By blending modified epoxy butyl hydroxyl rubber with silicone rubber raw rubber, introducing nano reinforcement filler and modifying treatment, and dopamine-modified glass fiber cloth, the problem of insufficient mechanical properties, mechanical properties and interface bonding force of silicone glass fiber cloth composite materials is solved, and an insulated silicone glass fiber cloth composite material with high tensile strength and long service life is achieved.

CN119842235AInactive Publication Date: 2025-04-18NANTONG YANGZI RUBBER & PLASTIC
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510129964.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-05
Publication Date
2025-04-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art cannot effectively improve the mechanical properties, mechanical properties, uniform distribution of nano reinforcement fillers and the interface bonding between the glass fiber cloth and the silicone rubber composite material, resulting in low bonding performance, easy material damage, and short service life.

Method used

By blending modified epoxy butyl hydroxyl rubber with silicone rubber raw rubber to form a co-crosslinking network, nano reinforcement filler is introduced and its compatibility with silicone rubber is improved through modification treatment, and dopamine-modified glass fiber cloth increases its surface roughness and surface area to enhance interface binding force.

Benefits of technology

The tensile strength, mechanical properties and thermal stability of the silicone glass fiber cloth composite material are significantly improved, and the overall performance and service life of the material are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119842235A_ABST
    Figure CN119842235A_ABST
Patent Text Reader

Abstract

The invention discloses an insulating silica gel glass fabric composite material with high tensile strength, and relates to the technical field of composite materials. The silicone rubber composite material comprises the following components in parts by weight: 100 parts of raw silicone rubber, 5-15 parts of modified epoxy hydroxyl-terminated polybutadiene, 20-40 parts of nano reinforcing filler, 1-5 parts of a cross-linking agent, 1-5 parts of a plasticizer and 1-2 parts of a catalyst. According to the invention, the modified epoxy hydroxyl-terminated polybutadiene and the raw silicone rubber are blended, so that the modified epoxy hydroxyl-terminated polybutadiene and the raw silicone rubber form a co-crosslinking network, the crosslinking density of the silicone rubber composite material is increased, the adhesive property of the silicone rubber composite material is improved, and the function of improving the mechanical property of the silicone rubber glass fabric composite material is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite materials, in particular to an insulating silicone glass fiber cloth composite material with high tensile strength. Background Art

[0002] Glass fiber cloth, also known as glass fiber cloth, is a fabric made of glass fiber, which has the characteristics of high temperature resistance, corrosion resistance and high strength. Silicone rubber is a polymer material with excellent weather resistance, high and low temperature resistance, chemical corrosion resistance and electrical insulation, and is widely used in electrical insulation, sealing, protection and other fields.

[0003] With glass fiber cloth as the base material, silicone rubber is coated on the surface of glass fiber cloth to obtain a composite material with high tensile strength. Since the bonding performance of silicone rubber will affect the mechanical properties of the composite material, when the composite material is subjected to tensile force, the bonding force between the glass fiber cloth and silicone rubber is insufficient to withstand the external force, resulting in a decrease in the tensile strength of the composite material, affecting the overall performance of the composite material. Therefore, an insulating silicone glass fiber cloth composite material with high tensile strength is extremely important.

[0004] 1. Patent document CN116581185B discloses a graphite-coated glass fiber cloth composite material. The above patent achieves the dual effects of fire prevention and anti-static, achieves good effects through a variety of flame retardant methods, and reduces the amount of smoke. However, the above patent cannot achieve the function of improving the mechanical properties of the silicone glass fiber cloth composite material.

[0005] 2. Patent document CN102675727B discloses a high-strength polypropylene glass fiber composite material and a preparation method thereof. The above patent achieves high strength, dimensional stability, creep resistance, and excellent appearance of the material, but the above patent cannot achieve the function of improving the mechanical properties of the silicone glass fiber cloth composite material.

[0006] 3. Patent document CN106366522B discloses a glass fiber-synthetic resin composite material and its preparation process. The above patent achieves improved waterproofness of the composite material, and has ideal bending and impact strength and good mechanical strength. However, the above patent cannot achieve the function of uniform distribution of nano-reinforcing fillers in silicone rubber composite materials.

[0007] 4. Patent document CN111576040B discloses a surface treatment liquid for ultra-thin electronic glass fiber cloth and a preparation method thereof. The above patent improves the heat resistance and ion migration resistance of the electronic glass fiber cloth, but the above patent cannot improve the interface bonding strength between the glass fiber cloth and the silicone rubber composite material.

[0008] In summary, the above patents cannot achieve the function of improving the mechanical properties of silicone glass fiber cloth composite materials, cannot achieve the function of improving the mechanical properties of silicone glass fiber cloth composite materials, cannot achieve the function of uniformly distributing nano-reinforcement fillers in silicone rubber composite materials, and cannot achieve the function of improving the interface bonding force between glass fiber cloth and silicone rubber composite materials, resulting in the problems of low bonding performance of silicone rubber composite materials, easy damage of silicone glass fiber cloth composite materials, and short service life; To this end, the present application proposes an insulating silicone glass fiber cloth composite material with high tensile strength, which can improve the mechanical properties of the silicone glass fiber cloth composite material, achieve the function of uniformly distributing nano-reinforcing fillers in the silicone rubber composite material, and improve the interface bonding force between the glass fiber cloth and the silicone rubber composite material. Summary of the invention

[0009] The object of the present invention is to provide an insulating silicone glass fiber cloth composite material with high tensile strength to solve the technical problems proposed in the above background technology that the mechanical properties of the silicone glass fiber cloth composite material cannot be improved, the mechanical properties of the silicone glass fiber cloth composite material cannot be improved, the uniform distribution of nano-reinforcing fillers in the silicone rubber composite material cannot be achieved, and the interface bonding force between the glass fiber cloth and the silicone rubber composite material cannot be improved, resulting in low bonding performance of the silicone rubber composite material, easy damage of the silicone glass fiber cloth composite material, and short service life.

[0010] To achieve the above object, the present invention provides the following technical solution: an insulating silicone glass fiber cloth composite material with high tensile strength, comprising a modified glass fiber cloth and a silicone rubber composite material, wherein both sides of the modified glass fiber cloth are coated with a silicone rubber composite material, wherein the silicone rubber composite material comprises the following components by weight: 100 parts of silicone rubber raw rubber, 5-15 parts of modified epoxy butyl rubber, 20-40 parts of nano-reinforcement filler, 1-5 parts of a cross-linking agent, 1-5 parts of a plasticizer, and 1-2 parts of a catalyst, and the preparation method of the silicone rubber composite material comprises the following steps: S1. Put the silicone rubber and modified epoxy hydroxybutane rubber into a high-speed mixer, rotate at 2000 r / min, mix for 2 min, add nano reinforcing filler, slowly increase the speed from 1500 r / min to 2500 r / min, and mix for 5 min; S2. Take out the rubber material in the high-speed mixer, place the rubber material in a constant temperature blast oven, cool it to room temperature, add the rubber material, crosslinking agent, plasticizer and catalyst cooled to room temperature into the high-speed mixer, rotate at 2500r / min, mix for 1min, and obtain a silicone rubber composite material.

[0011] Preferably, the preparation method of the modified hydroxybutyl epoxy adhesive comprises the following steps: Pour epoxy butadiene hydroxy rubber and aminopropyl triethoxysilane into a reaction container, and place the reaction container in a vacuum drying oven for drying; The reaction container is filled with nitrogen, heated and vacuumed, and cooled to room temperature to obtain modified epoxy hydroxybutyl rubber.

[0012] Preferably, the preparation method of the nano reinforcing filler comprises the following steps: Pour citric acid into deionized water to prepare a citric acid solution, add the modified nano zinc oxide into the citric acid solution, use an ultrasonic disperser to disperse for 2 hours, perform ultrasonic dispersion treatment, and obtain a mixed solution; Add water glass and deionized water to the reaction container, stir evenly, then add ethanol dropwise, place the reaction container in a water bath, heat to 85°C, stir with a magnetic stirrer, and add the mixed solution dropwise to the reaction container; A sulfuric acid solution is added to a reaction container, and after 0.5 hours, anhydrous ethanol is added to the reaction container to wash the reaction solution. The washed product is placed in an oven for drying to obtain a nano-composite material, and the nano-composite material is modified using 3-aminopropyltriethoxysilane to obtain a nano-reinforcing filler.

[0013] Preferably, the modification process of the nanocomposite material comprises the following steps: Dissolving 3-aminopropyltriethoxysilane in deionized water, adding citric acid, and adjusting the pH of the solution to 3 to obtain a 3-aminopropyltriethoxysilane aqueous solution; The nanocomposite material was added to the ethanol solution and dispersed for 30 min using an ultrasonic disperser to obtain a dispersion; The 3-aminopropyltriethoxysilane aqueous solution and the dispersion were mixed and placed in a water bath, heated to 60° C., and stirred using a magnetic stirrer to obtain a nano-reinforced filler.

[0014] Preferably, the preparation method of the modified nano zinc oxide comprises the following steps: Pour zinc oxide into deionized water, add hexadecyltrimethylammonium bromide, stir with a magnetic stirrer for 1 hour, place the stirred solution in an ultrasonic disperser, disperse with an ultrasonic disperser for 1 hour, and repeat the stirring and ultrasonic dispersion steps twice; The treated solution is poured into a suction filtration device for suction filtration, washed with ethanol and deionized water, and the washed product is placed in an oven for drying to obtain modified nano zinc oxide.

[0015] Preferably, the preparation method of the modified glass fiber cloth comprises the following steps: Dissolving aniline methyl triethoxysilane in an ethanol solution, adding a sodium hydroxide solution, and adjusting the pH to 8 to obtain an ethanol mixed solution; The glass fiber cloth is treated with a dopamine solution to obtain a dopamine-modified glass fiber cloth. The dopamine-modified glass fiber cloth is immersed in an ethanol mixed solution and heated in a 60° C. water bath for 24 hours to obtain a modified glass fiber cloth.

[0016] Preferably, the method for preparing the dopamine-modified glass fiber cloth comprises the following steps: Dissolve tris(hydroxymethyl)aminomethane in deionized water, add citric acid, adjust the pH to 8, and add dopamine to obtain a dopamine solution; The glass fiber cloth was soaked in an ethanol solution for 1 hour, and the soaked glass fiber cloth was washed with distilled water. The washed glass fiber cloth was soaked in a dopamine solution for 48 hours, and the glass fiber cloth was washed with distilled water again. The glass fiber cloth was placed in a vacuum drying oven and dried for 1 hour to obtain a dopamine-modified glass fiber cloth.

[0017] Preferably, the silicone rubber raw rubber is selected from one of polymethylethylvinylsiloxane, polydiethylsiloxane, polydimethylsiloxane and polydimethyldiphenylsiloxane.

[0018] Preferably, the catalyst is dibutyltin dilaurate and the crosslinking agent is ethyl orthosilicate.

[0019] Preferably, the plasticizer is selected from dibutyl phthalate, dioctyl phthalate, and dimethyl silicone oil.

[0020] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention blends modified epoxy hydroxybutyl rubber and silicone rubber raw rubber to form a co-crosslinking network, thereby increasing the crosslinking density of the silicone rubber composite material, improving the bonding performance of the silicone rubber composite material, and achieving the function of improving the mechanical properties of the silicone glass fiber cloth composite material; 2. The present invention improves the mechanical properties of the silicone glass fiber cloth composite material by introducing nano-reinforced fillers, and enhances the compatibility and interface bonding force between the nano-reinforced fillers and the silicone rubber matrix by modifying the nano-reinforced fillers loaded with silicon dioxide, thereby achieving the function of improving the mechanical properties of the silicone glass fiber cloth composite material; 3. The present invention modifies zinc oxide so that silicon dioxide is evenly dispersed on the surface of zinc oxide, thereby preventing silicon dioxide from agglomerating and achieving a uniform distribution function of nano-reinforcement fillers in the silicone rubber composite material. Zinc oxide captures and neutralizes acidic groups in silicone rubber, slowing down the degradation rate of silicone rubber and improving the thermal stability of the silicone rubber composite material. 4. The present invention improves the surface roughness and surface area of ​​the glass fiber cloth by modifying the glass fiber cloth with dopamine and modifying it again with aniline methyl triethoxysilane, thereby improving the interface bonding force between the glass fiber cloth and the silicone rubber composite material and improving the overall performance of the insulating silicone glass fiber cloth composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a schematic diagram of the preparation process of the silicone rubber composite material of the present invention; Figure 2 The schematic diagram of the preparation process of the modified epoxy hydroxybutane rubber of the present invention; Figure 3 This is a schematic diagram of the preparation process of the nano-reinforced filler of the present invention; Figure 4 It is a schematic diagram of the modification process of the nanocomposite material of the present invention; Figure 5 This is a schematic diagram of the preparation process of modified nano zinc oxide of the present invention; Figure 6 This is a schematic diagram of the preparation process of the modified glass fiber cloth of the present invention; Figure 7 This is a schematic diagram of the glass fiber dopamine modification process of the present invention; Figure 8 It is a schematic diagram of the silicone rubber raw rubber of the present invention. DETAILED DESCRIPTION

[0022] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] Example 1, please refer to Figure 1 , Figure 2 and Figure 8 , an insulating silicone glass fiber cloth composite material with high tensile strength, comprising a modified glass fiber cloth and a silicone rubber composite material, wherein both sides of the modified glass fiber cloth are coated with a silicone rubber composite material, wherein the silicone rubber composite material comprises the following components by weight: 100 parts of silicone rubber raw rubber, 15 parts of modified epoxy butyl rubber, 40 parts of nano-reinforcement filler, 5 parts of tetraethyl orthosilicate, 5 parts of dimethyl silicone oil, and 2 parts of dibutyltin dilaurate, and the preparation method of the silicone rubber composite material comprises the following steps: Pour epoxy butyl hydroxy rubber and aminopropyl triethoxysilane into a reaction container, place the reaction container in a vacuum drying oven for drying, fill the reaction container with nitrogen, heat and evacuate, and cool to room temperature to obtain modified epoxy butyl hydroxy rubber; Put the silicone rubber and modified epoxy hydroxybutyl rubber into a high-speed mixer, mix at a speed of 2000r / min for 2min, add nano-reinforcement filler, slowly increase the speed from 1500r / min to 2500r / min, and mix for 5min; The rubber material in the high-speed mixer was taken out, placed in a constant temperature blast oven, cooled to room temperature, and the rubber material, crosslinking agent, plasticizer and catalyst cooled to room temperature were added to the high-speed mixer at a speed of 2500 r / min and mixed for 1 min to obtain a silicone rubber composite material.

[0024] Furthermore, the epoxy hydroxybutane rubber is modified by aminopropyltriethoxysilane, and aminosilane is introduced into the molecular chain of the epoxy hydroxybutane rubber. Under the action of the catalyst dibutyltin dilaurate, the ethoxy group in the aminosilane molecule undergoes a hydrolysis reaction to generate silanol groups, which undergo a condensation reaction with the silanol groups in the silicone rubber raw rubber to form cross-linked bonds, so that the cross-linking sites on the modified epoxy hydroxybutane rubber chain segments and the silanol groups in the silicone rubber raw rubber are interconnected through a condensation reaction to form a co-cross-linked network, thereby increasing the cross-linking density of the silicone rubber composite material, improving the overall performance of the silicone rubber composite material, and enabling the silicone rubber composite material to better disperse stress when subjected to external forces, thereby improving the tensile strength and toughness of the silicone rubber composite material. At the same time, the modified epoxy hydroxybutane rubber has excellent adhesion, and blending the modified epoxy hydroxybutane rubber and silicone rubber raw rubber can improve the adhesion performance of the silicone rubber composite material.

[0025] Example 2, please refer to Figure 1 , Figure 3 , Figure 4 and Figure 8 , an insulating silicone glass fiber cloth composite material with high tensile strength, comprising a modified glass fiber cloth and a silicone rubber composite material, wherein both sides of the modified glass fiber cloth are coated with a silicone rubber composite material, wherein the silicone rubber composite material comprises the following components by weight: 100 parts of silicone rubber raw rubber, 15 parts of modified epoxy butyl rubber, 30 parts of nano-reinforcement filler, 5 parts of tetraethyl orthosilicate, 5 parts of dimethyl silicone oil, and 2 parts of dibutyltin dilaurate, and the preparation method of the silicone rubber composite material comprises the following steps: Pour citric acid into deionized water to prepare a citric acid solution, add modified nano zinc oxide to the citric acid solution, use an ultrasonic disperser to disperse for 2 hours, perform ultrasonic dispersion treatment to obtain a mixed solution, add water glass and deionized water to a reaction container, stir evenly and then drop ethanol, place the reaction container in a water bath, heat to 85°C, use a magnetic stirrer to stir, drop the mixed solution into the reaction container, add sulfuric acid solution to the reaction container, add anhydrous ethanol to the reaction container after 0.5 hours, wash the reaction solution, place the washed product in an oven, and dry it to obtain a nanocomposite material; Dissolve 3-aminopropyltriethoxysilane in deionized water, add citric acid, adjust the pH of the solution to 3, obtain a 3-aminopropyltriethoxysilane aqueous solution, add the nanocomposite material to the ethanol solution, use an ultrasonic disperser to disperse for 30 minutes to obtain a dispersion, mix the 3-aminopropyltriethoxysilane aqueous solution and the dispersion, place in a water bath, heat to 60° C., and stir with a magnetic stirrer to obtain a nano reinforcing filler; Put the silicone rubber and modified epoxy hydroxybutyl rubber into a high-speed mixer, mix at a speed of 2000r / min for 2min, add nano-reinforcement filler, slowly increase the speed from 1500r / min to 2500r / min, and mix for 5min; The rubber material in the high-speed mixer was taken out, placed in a constant temperature blast oven, cooled to room temperature, and the rubber material, crosslinking agent, plasticizer and catalyst cooled to room temperature were added to the high-speed mixer at a speed of 2500 r / min and mixed for 1 min to obtain a silicone rubber composite material.

[0026] Furthermore, the nanocomposite material is a composite material of zinc oxide loaded with silicon dioxide. Since the surface of silicon dioxide is rich in hydroxyl groups, the hydroxyl groups strengthen the interaction force between silicon dioxide particles by forming hydrogen bonds, thereby causing the silicon dioxide particles to agglomerate. The nanocomposite material of zinc oxide loaded with silicon dioxide is modified by 3-aminopropyltriethoxysilane. The ethoxy groups in the molecular chain of 3-aminopropyltriethoxysilane react with the hydroxyl groups on the surface of silicon dioxide to form covalent bonds, thereby reducing the number of hydroxyl groups on the surface of silicon dioxide, thereby reducing the hydrophilicity of the surface of the nanoreinforced filler, and enhancing the compatibility of the nanoreinforced filler with the silicone rubber matrix. The overall mechanical properties and tensile strength of the silicone rubber composite material are improved by improving the overall dispersibility of the nano-reinforcing filler, making the nano-reinforcing filler dispersed more evenly in the silicone rubber matrix and reducing the agglomeration phenomenon, thereby improving the reinforcement effect. At the same time, the silicon dioxide is composited with zinc oxide, so that the silicon dioxide is coated on the surface of zinc oxide, thereby increasing the specific surface area of ​​the nano-reinforcing filler and increasing the surface energy, thereby improving the dispersibility and stability of the nano-reinforcing filler in the silicone rubber matrix, further reducing the agglomeration phenomenon, and making the nano-reinforcing filler more evenly distributed in the silicone rubber matrix, thereby improving the overall performance of the silicone rubber composite material.

[0027] Example 3, please refer to Figure 1 , Figure 3 , Figure 5 and Figure 8, an insulating silicone glass fiber cloth composite material with high tensile strength, comprising a modified glass fiber cloth and a silicone rubber composite material, wherein both sides of the modified glass fiber cloth are coated with a silicone rubber composite material, wherein the silicone rubber composite material comprises the following components by weight: 100 parts of silicone rubber raw rubber, 15 parts of modified epoxy butyl rubber, 20 parts of nano-reinforcement filler, 5 parts of tetraethyl orthosilicate, 5 parts of dimethyl silicone oil, and 2 parts of dibutyltin dilaurate, and the preparation method of the silicone rubber composite material comprises the following steps: Pour zinc oxide into deionized water, add hexadecyltrimethylammonium bromide, stir with a magnetic stirrer for 1 hour, place the stirred solution in an ultrasonic disperser, disperse with the ultrasonic disperser for 1 hour, repeat the stirring and ultrasonic dispersion steps twice, pour the treated solution into a suction filtration device, perform suction filtration, wash with ethanol and deionized water, place the washed product in an oven, and dry it to obtain modified nano zinc oxide; Pour citric acid into deionized water to prepare a citric acid solution, add modified nano zinc oxide to the citric acid solution, use an ultrasonic disperser to disperse for 2 hours, perform ultrasonic dispersion treatment to obtain a mixed solution, add water glass and deionized water to a reaction container, stir evenly and then drop ethanol, place the reaction container in a water bath, heat to 85°C, use a magnetic stirrer to stir, drop the mixed solution into the reaction container, add sulfuric acid solution to the reaction container, add anhydrous ethanol to the reaction container after 0.5 hours, wash the reaction solution, place the washed product in an oven, dry it to obtain a nano composite material, modify the nano composite material with 3-aminopropyltriethoxysilane to obtain a nano reinforcing filler; Put the silicone rubber and modified epoxy hydroxybutyl rubber into a high-speed mixer, mix at a speed of 2000r / min for 2min, add nano-reinforcement filler, slowly increase the speed from 1500r / min to 2500r / min, and mix for 5min; The rubber material in the high-speed mixer was taken out, placed in a constant temperature blast oven, cooled to room temperature, and the rubber material, crosslinking agent, plasticizer and catalyst cooled to room temperature were added to the high-speed mixer at a speed of 2500 r / min and mixed for 1 min to obtain a silicone rubber composite material.

[0028] Furthermore, the surface of zinc oxide is modified by hexadecyltrimethylammonium bromide so that the surface of the modified zinc oxide carries a positive charge, so that silicate ions, the precursor of silicon dioxide, are adsorbed on the surface of zinc oxide, and silicon dioxide nanoparticles are grown in situ on the surface of zinc oxide so that silicon dioxide is evenly dispersed on the surface of zinc oxide, thereby preventing the agglomeration of silicon dioxide, improving the dispersibility of silicon dioxide, and making the nano-reinforcing filler more evenly distributed in the silicone rubber composite material, thereby enhancing the overall performance of the silicone rubber composite material. At the same time, silicone rubber will produce acidic groups during the degradation process, and zinc oxide can effectively capture and neutralize the acidic groups in silicone rubber, thereby slowing down the degradation rate of silicone rubber, extending the service life of the composite material, and improving the thermal stability of the silicone rubber composite material.

[0029] Example 4, please refer to Figure 1 , Figure 6 , Figure 7 and Figure 8 A high tensile strength insulating silicone glass fiber cloth composite material, comprising a modified glass fiber cloth and a silicone rubber composite material, wherein both sides of the modified glass fiber cloth are coated with a silicone rubber composite material, wherein the silicone rubber composite material comprises the following components by weight: 100 parts of silicone rubber raw rubber, 10 parts of modified epoxy butyl rubber, 30 parts of nano-reinforcement filler, 5 parts of tetraethyl orthosilicate, 5 parts of dimethyl silicone oil, and 2 parts of dibutyltin dilaurate. The preparation method of the silicone rubber composite material comprises the following steps: Put the silicone rubber and modified epoxy hydroxybutyl rubber into a high-speed mixer, mix at a speed of 2000r / min for 2min, add nano-reinforcement filler, slowly increase the speed from 1500r / min to 2500r / min, and mix for 5min; The rubber material in the high-speed mixer was taken out, placed in a constant temperature blast oven, cooled to room temperature, and the rubber material, crosslinking agent, plasticizer and catalyst cooled to room temperature were added to the high-speed mixer at a speed of 2500 r / min and mixed for 1 min to obtain a silicone rubber composite material.

[0030] Example 5, please refer to Figure 1 and Figure 8 , an insulating silicone glass fiber cloth composite material with high tensile strength, comprising a modified glass fiber cloth and a silicone rubber composite material, wherein both sides of the modified glass fiber cloth are coated with a silicone rubber composite material, wherein the silicone rubber composite material comprises the following components by weight: 100 parts of silicone rubber raw rubber, 5 parts of modified epoxy butyl rubber, 30 parts of nano-reinforcement filler, 5 parts of tetraethyl orthosilicate, 5 parts of dimethyl silicone oil, and 2 parts of dibutyltin dilaurate, and the preparation method of the silicone rubber composite material comprises the following steps: Put the silicone rubber and modified epoxy hydroxybutyl rubber into a high-speed mixer, mix at a speed of 2000r / min for 2min, add nano-reinforcement filler, slowly increase the speed from 1500r / min to 2500r / min, and mix for 5min; The rubber material in the high-speed mixer was taken out, placed in a constant temperature blast oven, cooled to room temperature, and the rubber material, crosslinking agent, plasticizer and catalyst cooled to room temperature were added to the high-speed mixer at a speed of 2500 r / min and mixed for 1 min to obtain a silicone rubber composite material.

[0031] Example 6, please refer to Figure 1 and Figure 8 , an insulating silicone glass fiber cloth composite material with high tensile strength, comprising a modified glass fiber cloth and a silicone rubber composite material, wherein the silicone rubber composite material comprises the following components by weight: 100 parts of silicone rubber raw rubber, 15 parts of modified epoxy hydroxybutyl rubber, 40 parts of nano-reinforcement filler, 1 part of a cross-linking agent, 1 part of a plasticizer, and 1 part of a catalyst, wherein both sides of the modified glass fiber cloth are coated with the silicone rubber composite material, and the preparation method of the modified glass fiber cloth comprises the following steps: Dissolve tris(hydroxymethyl)aminomethane in deionized water, add citric acid, adjust the pH to 8, add dopamine to obtain a dopamine solution, soak the glass fiber cloth in the ethanol solution for 1 hour, wash the soaked glass fiber cloth with distilled water, soak the washed glass fiber cloth in the dopamine solution for 48 hours, wash the glass fiber cloth with distilled water again, place the glass fiber cloth in a vacuum drying oven, and dry for 1 hour to obtain dopamine-modified glass fiber cloth; Aniline methyl triethoxysilane was dissolved in an ethanol solution, and a sodium hydroxide solution was added to adjust the pH to 8 to obtain an ethanol mixed solution. Dopamine-modified glass fiber cloth was immersed in the ethanol mixed solution and heated in a 60° C. water bath for 24 hours to obtain a modified glass fiber cloth.

[0032] Furthermore, the amino and hydroxyl groups in the dopamine structure form chemical bonds with the hydroxyl groups on the surface of the glass fiber cloth, so that the dopamine molecules are adsorbed on the surface of the glass fiber cloth, increasing the surface roughness and surface area of ​​the glass fiber cloth, thereby improving the interfacial bonding force between the glass fiber cloth and the silicone rubber composite material. The introduction of dopamine can improve the polarity of the surface of the glass fiber cloth, making the glass fiber cloth more easily infiltrated by the silicone rubber composite material, thereby reducing the formation of bubbles and defects during the coating process and improving the overall quality of the silicone glass fiber cloth composite material; the silane group in the aniline methyl triethoxysilane molecule undergoes hydrolysis and condensation reactions with the silicon atoms in the silicone rubber matrix to form chemical bonds; the amino group in the aniline methyl triethoxysilane molecule interacts with the surface of the glass fiber cloth modified by dopamine, thereby further enhancing the interfacial bonding force between the glass fiber cloth and the silicone rubber composite material, making the connection between the glass fiber cloth and the silicone rubber composite material tighter, and through the modification of dopamine and aniline methyl triethoxysilane, the interfacial bonding force between the glass fiber cloth and the silicone rubber composite material is enhanced, thereby improving the tensile strength, tear strength and wear resistance of the insulating silicone glass fiber cloth composite material.

[0033] Comparative Example 1, an insulating silicone glass fiber cloth composite material with high tensile strength, comprising a modified glass fiber cloth and a silicone rubber composite material, wherein both sides of the modified glass fiber cloth are coated with a silicone rubber composite material, wherein the silicone rubber composite material comprises the following components by weight: 100 parts of silicone rubber raw rubber, 15 parts of epoxy butyl rubber, 40 parts of nano-reinforcement filler, 5 parts of tetraethyl orthosilicate, 5 parts of dimethyl silicone oil, and 2 parts of dibutyltin dilaurate, and the preparation method of the silicone rubber composite material comprises the following steps: Put the silicone rubber and epoxy hydroxybutane rubber into a high-speed mixer, mix at a speed of 2000r / min for 2min, add nano-reinforcement filler, slowly increase the speed from 1500r / min to 2500r / min, and mix for 5min; The rubber material in the high-speed mixer was taken out, placed in a constant temperature blast oven, cooled to room temperature, and the rubber material, crosslinking agent, plasticizer and catalyst cooled to room temperature were added to the high-speed mixer at a speed of 2500 r / min and mixed for 1 min to obtain a silicone rubber composite material.

[0034] Comparative Example 2, an insulating silicone glass fiber cloth composite material with high tensile strength, comprising a modified glass fiber cloth and a silicone rubber composite material, wherein both sides of the modified glass fiber cloth are coated with a silicone rubber composite material, wherein the silicone rubber composite material comprises the following components by weight: 100 parts of silicone rubber raw rubber, 15 parts of modified epoxy butyl rubber, 40 parts of nanocomposite material, 5 parts of tetraethyl orthosilicate, 5 parts of dimethyl silicone oil, and 2 parts of dibutyltin dilaurate, and the preparation method of the silicone rubber composite material comprises the following steps: Pour citric acid into deionized water to prepare a citric acid solution, add modified nano zinc oxide to the citric acid solution, use an ultrasonic disperser to disperse for 2 hours, perform ultrasonic dispersion treatment to obtain a mixed solution, add water glass and deionized water to a reaction container, stir evenly and then drop ethanol, place the reaction container in a water bath, heat to 85°C, use a magnetic stirrer to stir, drop the mixed solution into the reaction container, add sulfuric acid solution to the reaction container, add anhydrous ethanol to the reaction container after 0.5 hours, wash the reaction solution, place the washed product in an oven, and dry it to obtain a nanocomposite material; Put the silicone rubber and modified epoxy hydroxybutyl rubber into a high-speed mixer, mix at a speed of 2000r / min for 2min, add nano-reinforcement filler, slowly increase the speed from 1500r / min to 2500r / min, and mix for 5min; The rubber material in the high-speed mixer was taken out, placed in a constant temperature blast oven, cooled to room temperature, and the rubber material, crosslinking agent, plasticizer and catalyst cooled to room temperature were added to the high-speed mixer at a speed of 2500 r / min and mixed for 1 min to obtain a silicone rubber composite material.

[0035] Comparative Example 3, an insulating silicone glass fiber cloth composite material with high tensile strength, comprising modified glass fiber cloth and silicone rubber composite material, wherein the silicone rubber composite material comprises the following components by weight: 100 parts of silicone rubber raw rubber, 15 parts of modified epoxy hydroxybutyl rubber, 40 parts of nano-reinforcement filler, 1 part of cross-linking agent, 1 part of plasticizer, and 1 part of catalyst, and both sides of the dopamine-modified glass fiber cloth are coated with silicone rubber composite material, and the preparation method of the dopamine-modified glass fiber cloth comprises the following steps: Dissolve tris(hydroxymethyl)aminomethane in deionized water, add citric acid, adjust the pH to 8, and add dopamine to obtain a dopamine solution; The glass fiber cloth was soaked in an ethanol solution for 1 hour, and the soaked glass fiber cloth was washed with distilled water. The washed glass fiber cloth was soaked in a dopamine solution for 48 hours, and the glass fiber cloth was washed with distilled water again. The glass fiber cloth was placed in a vacuum drying oven and dried for 1 hour to obtain a dopamine-modified glass fiber cloth.

[0036] Test 1 Tensile performance test: The glass fiber cloth coated with the silicone rubber composite material prepared in Examples 1-6 and Comparative Examples 1-3 was tested according to the national standard GB528-2009 method, and the tensile strength was recorded; Test 2 Adhesion performance test: The silicone rubber composite materials prepared in Examples 1-6 and Comparative Examples 1-3 were tested according to the national standard GB7124-2008 method, and the tensile shear strength was recorded; Test 3 Thermal stability test: The silicone rubber composite materials prepared in Examples 1-6 and Comparative Examples 1-3 were subjected to thermal stability analysis test using a differential thermal-thermogravimetric instrument to record the 5% weight loss temperature of the material.

[0037] Table 1 Test results of sample performance test Working principle: the amino functional group in aminopropyl triethoxysilane reacts with the epoxy group in epoxy butyl rubber to form a chemical bond, thereby enhancing the interfacial bonding force between epoxy butyl rubber and silicone rubber, improving the overall bonding performance of silicone rubber composite materials, and improving the compatibility between modified epoxy butyl rubber and silicone rubber raw rubber, thereby forming a uniform and stable silicone rubber composite structure, thereby improving the overall performance of silicone glass fiber cloth composite materials; The nano-reinforcing filler is a composite material of zinc oxide and silicon dioxide. The surface of zinc oxide is modified to make silicon dioxide evenly dispersed on the surface of zinc oxide. The composite material of zinc oxide and silicon dioxide is modified to reduce the number of hydroxyl groups on the surface of silicon dioxide, prevent the agglomeration of silicon dioxide, improve the dispersibility of the nano-reinforcing filler in silicone rubber, and improve the mechanical properties of the silicone rubber composite material. Zinc oxide can neutralize the acidic groups generated during the degradation of silicone rubber, thereby slowing down the degradation rate of silicone rubber and extending the service life of the rubber composite material. By modifying the glass fiber cloth with dopamine and modifying it again with aniline methyl triethoxysilane, the surface roughness and surface area of ​​the glass fiber cloth are improved, and the interface bonding force between the glass fiber cloth and the silicone rubber composite material is enhanced, thereby improving the tensile strength of the insulating silicone glass fiber cloth composite material.

[0038] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

Claims

1. An insulating silicone glass fiber cloth composite material with high tensile strength, characterized in that: The invention comprises a modified glass fiber cloth and a silicone rubber composite material, wherein both sides of the modified glass fiber cloth are coated with the silicone rubber composite material, and the silicone rubber composite material comprises the following components by weight: 100 parts of silicone rubber raw rubber, 5-15 parts of modified epoxy hydroxybutyl rubber, 20-40 parts of nano-reinforcement filler, 1-5 parts of cross-linking agent, 1-5 parts of plasticizer, and 1-2 parts of catalyst. The preparation method of the silicone rubber composite material comprises the following steps: S1. Put the silicone rubber and modified epoxy hydroxybutane rubber into a high-speed mixer, rotate at 2000 r / min, mix for 2 min, add nano reinforcing filler, slowly increase the speed from 1500 r / min to 2500 r / min, and mix for 5 min; S2. Take out the rubber material in the high-speed mixer, place the rubber material in a constant temperature blast oven, cool it to room temperature, add the rubber material, crosslinking agent, plasticizer and catalyst cooled to room temperature into the high-speed mixer, rotate at 2500r / min, mix for 1min, and obtain a silicone rubber composite material.

2. The insulating silicone glass fiber cloth composite material with high tensile strength according to claim 1, characterized in that: The preparation method of the modified epoxy hydroxybutane adhesive comprises the following steps: Pour epoxy butadiene hydroxy rubber and aminopropyl triethoxysilane into a reaction container, and place the reaction container in a vacuum drying oven for drying; The reaction container is filled with nitrogen, heated and vacuumed, and cooled to room temperature to obtain modified epoxy hydroxybutyl rubber.

3. The insulating silicone glass fiber cloth composite material with high tensile strength according to claim 1, characterized in that: The preparation method of the nano reinforcing filler comprises the following steps: Pour citric acid into deionized water to prepare a citric acid solution, add the modified nano zinc oxide into the citric acid solution, use an ultrasonic disperser to disperse for 2 hours, perform ultrasonic dispersion treatment, and obtain a mixed solution; Add water glass and deionized water to the reaction container, stir evenly, then add ethanol dropwise, place the reaction container in a water bath, heat to 85°C, stir with a magnetic stirrer, and add the mixed solution dropwise to the reaction container; A sulfuric acid solution is added to a reaction container, and after 0.5 hours, anhydrous ethanol is added to the reaction container to wash the reaction solution. The washed product is placed in an oven for drying to obtain a nano-composite material, and the nano-composite material is modified using 3-aminopropyltriethoxysilane to obtain a nano-reinforcing filler.

4. The insulating silicone glass fiber cloth composite material with high tensile strength according to claim 3, characterized in that: The modification process of the nanocomposite material comprises the following steps: Dissolving 3-aminopropyltriethoxysilane in deionized water, adding citric acid, and adjusting the pH of the solution to 3 to obtain a 3-aminopropyltriethoxysilane aqueous solution; The nanocomposite material was added to the ethanol solution and dispersed for 30 min using an ultrasonic disperser to obtain a dispersion; The 3-aminopropyltriethoxysilane aqueous solution and the dispersion were mixed and placed in a water bath, heated to 60° C., and stirred using a magnetic stirrer to obtain a nano-reinforced filler.

5. The insulating silicone glass fiber cloth composite material with high tensile strength according to claim 3, characterized in that: The preparation method of the modified nano zinc oxide comprises the following steps: Pour zinc oxide into deionized water, add hexadecyltrimethylammonium bromide, stir with a magnetic stirrer for 1 hour, place the stirred solution in an ultrasonic disperser, disperse with an ultrasonic disperser for 1 hour, and repeat the stirring and ultrasonic dispersion steps twice; The treated solution is poured into a suction filtration device for suction filtration, washed with ethanol and deionized water, and the washed product is placed in an oven for drying to obtain modified nano zinc oxide.

6. The insulating silicone glass fiber cloth composite material with high tensile strength according to claim 1, characterized in that: The preparation method of the modified glass fiber cloth comprises the following steps: Dissolving aniline methyl triethoxysilane in an ethanol solution, adding a sodium hydroxide solution, and adjusting the pH to 8 to obtain an ethanol mixed solution; The glass fiber cloth is treated with a dopamine solution to obtain a dopamine-modified glass fiber cloth. The dopamine-modified glass fiber cloth is immersed in an ethanol mixed solution and heated in a 60° C. water bath for 24 hours to obtain a modified glass fiber cloth.

7. The insulating silicone glass fiber cloth composite material with high tensile strength according to claim 6, characterized in that: The preparation method of the dopamine-modified glass fiber cloth comprises the following steps: Dissolve tris(hydroxymethyl)aminomethane in deionized water, add citric acid, adjust the pH to 8, and add dopamine to obtain a dopamine solution; The glass fiber cloth was soaked in an ethanol solution for 1 hour, and the soaked glass fiber cloth was washed with distilled water. The washed glass fiber cloth was soaked in a dopamine solution for 48 hours, and the glass fiber cloth was washed with distilled water again. The glass fiber cloth was placed in a vacuum drying oven and dried for 1 hour to obtain a dopamine-modified glass fiber cloth.

8. The insulating silicone glass fiber cloth composite material with high tensile strength according to claim 1, characterized in that: The silicone rubber raw rubber is selected from one of polymethylethylvinylsiloxane, polydiethylsiloxane, polydimethylsiloxane and polydimethyldiphenylsiloxane.

9. The insulating silicone glass fiber cloth composite material with high tensile strength according to claim 1, characterized in that: The catalyst is dibutyltin dilaurate, and the cross-linking agent is ethyl orthosilicate.

10. The insulating silicone glass fiber cloth composite material with high tensile strength according to claim 1, characterized in that: The plasticizer is selected from dibutyl phthalate, dioctyl phthalate, and dimethyl silicone oil.

Citation Information

Patent Citations

  • High-strength polypropylene fiberglass composite material and preparation method thereof

    CN102675727B

  • A kind of glass fiber-synthetic resin composite material and its preparation process

    CN106366522B

  • A surface treatment liquid for ultrathin electronic fiberglass cloth and its preparation method

    CN111576040B

  • A graphite-coated glass fiber cloth composite material

    CN116581185B

  • Modified two-component silicone sealant and preparation method thereof

    CN109971416A